Is the hybridization phenomenon traceable in the otolith and scale of extant Aphanius species? – A case study on hybrid offsprings of Aphanius farsicus X A. sophiae (Teleostei: Aphaniidae). (17th March 2020) - Masoudi, Mojtaba; Esmaeili, Hamid Reza; Teimori, Azad; Ebrahimi, Mehregan; Seifali, Mahvash
Abstract: The otolith and scale were analysed in the hybrid offsprings between two Aphanius species, that is, A. farsicus and A. sophiae to evaluate if they are suitable to trace hybridization. An artificial reciprocal hybridization was performed between two species. The hybrids of A. farsicus ♂ × A. sophiae ♀ had otoliths with long and pointed rostrum with a narrow depression in the middle of the ventral rim. The otoliths of hybrids between A. farsicus ♀ × A. sophiae ♂ were more close to A. sophiae ♂. As a result, the otolith contour of the hybrids was intermediate to those of the parents. Therefore, we suggest that some variations observed in the otoliths of Aphanius species may be resulted by hybridization particularly when they are sympatric or has geographic overlap. Also, no remarkable differences were found between the scales of hybrids and parents. This indicated that scale morphology and surface microstructures are not suitable for tracing the hybridization. If these species are sympatric due to possible translocation, it causes the genetic introgression of a native species through hybridization. This must be particularly considered in the conservation programme of endangered A. farsicus because artificial transplantation and consequent hybridization can lead to the extinction of this critically endangered species.